Birikim Dergisi çerçevesinde Türk Solu ve Arap Baharı - Özorpak, Muhamed Eren (My University, 2019)
kimse için şaşırtıcı bir sürecin başlangıcı oldu. Tunus’ta başlayan halk isyanları Mısır, Libya, Suriye’de kendi sınırlarını aşarak birbirinden farklı sonuçlar doğurdu. Halk isyanları Tunus, Mısır ve Libya’da rejimi devirmeyi başarırken, Suriye’de halen devam eden ve yüzbinlerin ölümüne neden olan bir iç savaşa dönüştü. Ortadoğu’da olup bitenler birçok ülke için beklenmedik ve tahmin edilemeyen bir olaylar zinciri olarak nitelendirildi. Arap Baharı sonrasında halk eylemleri, “dış güç odaklı” ve “kendi dinamiklerinden doğan tepki” olmak üzere iki temel fikir üzerinden anlamlandırılmaya çalışıldı.Ortadoğu’da olup bitenler bütün dünya kamuoyununum gündemine otururken, Türkiye’de de süreç gerek iktisadi gerekse siyasal ilişkilerinde etkisiyle yakinen takip edildi. Arap Baharı dünyada olduğu gibi birbirinden farklı bakış açıları ile yorumlanmıştır. 40 yılı aşkın aktif yayın hayatına sahip olan Birikim Dergisi de Arap Baharı olaylarını yakından izlemiş ve düzenli olarak konuyla ilgili kaleme alınmış yazılara dergide yer vermiştir. Bu çalışma Arap Baharı olaylarını Birikim Dergisi çerçevesinde inceleyerek, Birikim Çevresi’nin Arap Baharı’na bakış açısını ortaya koymayı hedeflemektedir.

The latest months of 2010 were the start of a surprising process to many due to the public protests which quickly multiplied in the Middle East. The nation-wide riots which started in Tunisia, spread over to Egypt, Libya and Syria with different results beyond their borders. The public protests accomplished to overthrow the existing regimes in Tunisia, Egypt and Libya whereas in Syria they resulted in a civil war which continues to date and has claimed the lives of hundred-thousands of people. Events which unfolded in the Middle East were described as an unexpected and unpredictable chain of events. The public protests following the Arab Spring were interpreted in two main arguments which are “caused by external powers” and “stemming from internal dynamics”.While the events in the Middle East occupied the agenda of the world, both the financial and political impact of the process was closely monitored in Turkey as well. The Arab Spring was interpreted in Turkey from many different perspectives similar to the rest of the world. The Birikim Journal with its leftist approaches which has been actively issuing volumes for over 40 years, closely monitored the issue also and regularly featured articles on the topic. This study aims to unveil the perspective of the Birikim circle on the Arab Spring by studying the Arab Spring in the framework of the Arab Spring.
Keywords: Arap Baharı; Birikim Dergisi; Birikim Journal; Islamic countries; İslam ülkeleri; Middle East; Orta Doğu; Turkish Left View; Türk Solu Arab Spring